Peran Manajemen Risiko dalam Implementasi Kebijakan Keberlanjutan di Era Digital - Eben Eser Nainggolan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology has had a significant impact on various sectors, including risk management and sustainability. In this context, risk management plays a crucial role in implementing sustainability management policies, particularly in the digital era characterized by the use of advanced technologies such as artificial intelligence, blockchain, and big data analytics. This study aims to explore how risk management can support sustainability policies by leveraging digital technology. Using a literature analysis approach, this paper examines various aspects, including the challenges and opportunities faced by organizations in integrating risk management with sustainability strategies. The findings indicate that organizations that successfully adopt effective risk management can improve their sustainability performance, reduce environmental impacts, and increase competitiveness in the global market. Furthermore, this paper identifies the importance of collaboration between the public and private sectors in creating a framework that supports sustainability. Thus, this study contributes to the understanding of the role of risk management in supporting sustainability policies in the digital era and offers recommendations for practitioners and policymakers to improve the effectiveness of their sustainability strategies.